Submillisecond protein folding kinetics studied by ultrarapid mixing - Chan, Chi-Kin (The National Academy of Sciences of the USA, 1997)
An ultrarapid-mixing continuous-flow method has been developed to study submillisecond folding of chemically denatured proteins. Turbulent flow created by pumping solutions through a small gap dilutes the denaturant in tens of microseconds. We have used this method to study cytochrome c folding kinetics in the previously inaccessible time range 80 μs to 3 ms. To eliminate the heme–ligand exchange chemistry that complicates and slows the folding kinetics by trapping misfolded structures, measurements were made with the imidazole complex. Fluorescence quenching due to excitation energy transfer from the tryptophan to the heme was used to monitor the distance between these groups. The fluorescence decrease is biphasic. There is an unresolved process with τ < 50 μs, followed by a slower, exponential process with τ = 600 μs at the lowest denaturant concentration (0.2 M guanidine hydrochloride). These kinetics are interpreted as a barrier-free, partial collapse to the new equilibrium unfolded state at the lower denaturant concentration, followed by slower crossing of a free energy barrier separating the unfolded and folded states. The results raise several fundamental issues concerning the dynamics of collapse and barrier crossings in protein folding.